THE EFFECT OF THE SOAKING PERIOD IN NATURAL FEED TATTS of Chaetoceros sp. ON THE GROWTH AND VIABILITY OF PEARL CLASS (Pinctada maxima) SEEDS - Satria Fajry; Dewi Nuraini Setyowati; Alis Mukhlis (Journal of Fish Health, 2022)
Pearl oysters are a marine aquaculture commodity with high economic value. However, there are still many obstacles in pearl oyster cultivation activities, such as the need for quality seeds. This study aims to determine the effect of immersing pearl seeds in natural feed tanks of Chaetocheros sp. with different immersion periods on the growth and survival rate of pearl oyster (Pinctada maxima) seeds. The method used in this study is an experimental method using a completely randomized design (CRD), with 5 treatments and 3 replications, namely A (control/without immersion), B (0.5 hours), C (1 hour), D (1, 5 Hours) and E (2 Hours). The results showed that soaking the seeds in natural feed tanks had a significant effect on the growth of the shell (dorsal-ventral) of the pearl oyster Pinctada maxima (p<0.05). The highest growth was achieved in the 2-hour immersion period with an absolute growth value of 1.67 mm, a relative growth of 68.49% from the initial size, and a daily specific growth rate of 3.31% per day. This method must be tested on larger pearl oyster seeds and using other natural feed species and various natural mixes (multi-species).